Respuesta :

Answer:   6

===================================================

Explanation:

Each point listed is of the form (x,y)

The input x is fed into the f(x) function to get a y = f(x) output.

Recall that the inverse function undoes everything the original function does.

This means that when we determine the inverse function for a list of points like this, we just swap each x and y.

So if

[tex]f = \{ (3.5, 2), (0,4), (1,5), (6,1) \}[/tex]

then,

[tex]f^{-1} = \{ (2,3.5), (4,0), (5,1), (1,6) \}[/tex]

Again all I've done is swap each x and y value.

From here, we look through the inverse function set and look for the point when x = 1. We see the point (1,6) is in the set.

Therefore, [tex]f^{-1}(1) = 6[/tex]